Are long-lasting nonspecific symptoms related to vitamin D deficiency among older adults living in nursing homes? - Rebeka Arnljots; Egill Snaebjörnsson Arnljots; Jörgen Thorn; Marie Elm; Michael Moore; Pär-Daniel Sundvall (BMC Geriatrics)
Abstract Background Confusion, restlessness, and fatigue are common among older adults living in nursing homes. These nonspecific symptoms are often treated with antibiotics since they are frequently misinterpreted as urinary tract infections. Therefore, it is crucial to investigate other potential causes of these nonspecific symptoms. Impaired cognitive function in older adults may be associated with vitamin D deficiency and could lead to nonspecific symptoms. Currently, it is unknown whether there is a correlation between nonspecific symptoms, often misinterpreted as acute cystitis, and vitamin D deficiency. Methods A cross-sectional study in which blood samples were collected from residents of 22 Swedish nursing homes for 25OHD (25-hydroxyvitamin D) analysis. Demographics and presence of nonspecific symptoms, such as: fatigue, restlessness, confusion, aggressiveness, reduced appetite, tendency to fall or a sense of not being oneself as well as symptom duration, were registered. Exclusion criteria: incontinence, dementia too severe to cooperate when taking a blood test, terminally ill or refusing participation. Logistic regressions were performed to determine if nonspecific symptoms persisting ≥ 3 months were associated with vitamin D deficiency. Results Out of 901 residents in 22 nursing homes blood samples were taken from 545 participants, of whom 370 (68%) were women. The mean age was 86 years (SD 6.9), and 55% (299/545) had dementia. The prevalence of symptoms persisting ≥ 3 months was: fatigue 49% (268/545), restlessness 50% (270/545), confusion 53% (287/545), agitation/anger 47% (258/545), reduced appetite 45% (247/545), tendency to fall 48% (260/545), and a sense of not being oneself 35% (191/545). The 25OHD concentrations did not differ between various nonspecific symptoms. When adjusting for age, gender and dementia there was no association between any of the nonspecific symptoms and 25OHD. Conclusions Nonspecific symptoms persisting ≥ 3 months and vitamin D deficiency were common among older adults living in nursing homes. However, there was no association between these long-lasting nonspecific symptoms and the concentration of vitamin D. In further research it is important to study other potential causes of nonspecific symptoms in older adults.